Prader-Willi Syndrome (PWS) (Journal of Armed Forces Medical College, Bangladesh, 2011)
An eleven-year-old boy reported with increasing body weight and appetite since birth. He is suffering from insulin dependent diabetes since ten years of age and underwent extensive investigation including MRI of brain. His physical findings, biochemical and MRI findings were consistent with Prader-Willi syndrome (PWS). DOI: 10.3329/jafmc.v6i2.7276JAFMC Bangladesh. Vol 6, No 2 (December) 2010 pp.46-47